2003
DOI: 10.3390/i4060335
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modelling for the Ground State Rotamerisation and Excited State Intramolecular Proton Transfer of 2-(2’-hydroxyphenyl)oxazole, 2-(2’-hydroxyphenyl)imidazole, 2-(2’-hydroxyphenyl)thiazole and Their Benzo Analogues

Abstract: Two series of compounds, one comprising of 2-(2′-hydroxyphenyl)benzoxazole (HBO), 2-(2′-hydroxyphenyl)benzimidazole (HBI), 2-(2′-hydroxyphenyl)benzothiazole (HBT), and the other of 2-(2′-hydroxyphenyl)oxazole (HPO), 2-(2′-hydroxyphenyl)imidazole (HPI) and 2-(2′-hydroxyphenyl)thiazole (HPT) are susceptible to ground state rotamerization as well as excited state intramolecular proton transfer (ESIPT) reactions. Some of these compounds show experimental evidence of the existence of two ground state conformers. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…In water, each hydrogen bonding site in HBO ( anti and syn tautomers) is solvated by two water molecules that are in direct contact with the OH group and the N/O heteroatom37. This particular solvation mechanism is supported by the stable planarity of the HBO backbone4142.…”
Section: Resultsmentioning
confidence: 99%
“…In water, each hydrogen bonding site in HBO ( anti and syn tautomers) is solvated by two water molecules that are in direct contact with the OH group and the N/O heteroatom37. This particular solvation mechanism is supported by the stable planarity of the HBO backbone4142.…”
Section: Resultsmentioning
confidence: 99%
“…Although the solvent effect on the ESIPT mechanism has been investigated experimentally [14][15][16] and theoretically [17][18][19][20][21] in several structures, a discussion concerning some amino 2-(2 0 -hydroxyphenyl)benzazole derivatives (Scheme 1) is nowadays particularly interesting since the amino group being strong electron donor in the excited state, the fluorescence spectrum of amino derivatives are more sensitive to the solvent polarity than the absorption spectrum [22]. These dyes have been used as probe to discuss hydrophobic-hydrophilic environments [23], for instance, in systems that use polymers for drug delivery [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence of HBT in the different environments is similar to that of HBO. Both molecules are reported to be planar in their crystal structures , and by semi‐empirical and ab initio calculations . The weaker hydrogen bond in HBT resulted in a very small concentration of the anion species in aqueous neutral solution as evidenced in Fig.…”
Section: Photophysics Of Hbxs In Solutionmentioning
confidence: 88%
“…In an aqueous medium, the tendency of water molecules to strongly associate with each other through intermolecular hydrogen bonds allows more than one molecule of water to form a solvent network or a solvent wire along which proton transfers can take place to and from the solute (45). This particular solvation mechanism is supported by the stable planarity of the HBO backbone (46,47). In a previous study, we found that two water molecules solvate the hydrogen-bonding site of the syn-enol tautomer in which HBO undergoes water-assisted tautomerization in the excited state to yield the syn-keto species (32).…”
Section: Comparative Studies Of Hbxs In Solutionmentioning
confidence: 99%